2018
DOI: 10.1039/c8ra04846k
|View full text |Cite
|
Sign up to set email alerts
|

EEG characteristic analysis of coach bus drivers based on brain connectivity as revealed via a graph theoretical network

Abstract: This study describes the detection of driving fatigue using the characteristics of brain networks in a real driving environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Hence, it is necessary to effectively relieve driving fatigue. Studies have shown that repetitive and monotonous external environmental information can easily lead human beings to be in a state of mental fatigue, in which our brain activity is inhibited [50,51,52]. In our study, we tried to stimulate human brain nerves repeatedly to keep them active all the time to combat mental fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is necessary to effectively relieve driving fatigue. Studies have shown that repetitive and monotonous external environmental information can easily lead human beings to be in a state of mental fatigue, in which our brain activity is inhibited [50,51,52]. In our study, we tried to stimulate human brain nerves repeatedly to keep them active all the time to combat mental fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, given that multichannel EEG signals are used, we define each electrode on the scalp surface as a network node (Step 2) We quantify the functional connectivity relationship between network nodes. One of the commonly used methods is Pearson's correlation coefficient [ 24 ]. The formula is shown as follows: where x i ( t ) and x j ( t ) are the sampling values of nodes i and j at time t , respectively; and are the average sampling values of nodes i and j , respectively; and N is the number of network nodes.…”
Section: Methodsmentioning
confidence: 99%
“…The commonly used methods are Pearson correlation coefficient, coherence spectrum, and mutual information. Pearson correlation coefficient is selected because of its better noise suppression and robustness compared with the other two methods [23]. The formula is as follows:…”
Section: Eeg Signal Featuresmentioning
confidence: 99%
“…Fast independent component analysis was used for denoising to obtain more pure EEG signals, ensuring the effectiveness of the extracted features in the subsequent work. The ERD/ERS phenomenon is related to the mu (8-12 Hz) and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) rhythms of EEG signals. However, some frequencies in the beta rhythm are the harmonic waves of the mu rhythm.…”
Section: Eeg Data Preprocessingmentioning
confidence: 99%